Food for Thought in Restaurant Reviews: Lifestyle journalism or an extension of marketing in UK and Australian newspapers. (2nd January 2019) - English, Peter; Fleischman, David
Abstract : Coverage of food journalism has increased in contemporary media and restaurant reviews are a regular feature in newspapers. The reaction to a rating of zero for a restaurant in The Weekend Australian newspaper in 2016 highlighted the role and expectations of critics. It also raised the issue of whether this form of lifestyle journalism included traditional journalistic objectives, or was influenced more by commercial factors. In this environment, it is therefore valuable to explore whether restaurant reviews are more aligned with detached journalism or an extension of marketing. Utilising a content analysis, this pilot study examines the ratings of food critics in four broadsheet/quality newspapers in Australia and the United Kingdom. During the three years of the data collection, 550 restaurant reviews were coded. The pattern of review marks suggested more supportive judgements than critical ones, and was consistent with the softer side of journalism.